Role of SDF‐1:CXCR4 in Impaired Post‐Myocardial Infarction Cardiac Repair in Diabetes. (9th November 2017) - Mayorga, Maritza E.; Kiedrowski, Matthew; McCallinhart, Patricia; Forudi, Farhad; Ockunzzi, Jeremiah; Weber, Kristal; Chilian, William; Penn, Marc S.; Dong, Feng
Abstract: Diabetes is a risk factor for worse outcomes following acute myocardial infarction (AMI). In this study, we tested the hypothesis that SDF‐1:CXCR4 expression is compromised in post‐AMI in diabetes, and that reversal of this defect can reverse the adverse effects of diabetes. Mesenchymal stem cells (MSC) isolated from green fluorescent protein (GFP) transgenic mice (control MSC) were induced to overexpress stromal cell‐derived factor‐1 (SDF‐1). SDF‐1 expression in control MSC and SDF‐1‐overexpressing MSC (SDF‐1:MSC) were quantified using enzyme‐linked immunosorbent assay (ELISA). AMI was induced on db/db and control mice. Mice were randomly selected to receive infusion of control MSC, SDF‐1:MSC, or saline into the border zone after AMI. Serial echocardiography was used to assess cardiac function. SDF‐1 and CXCR4 mRNA expression in the infarct zone of db/db mice and control mice were quantified. Compared to control mice, SDF‐1 levels were decreased 82%, 91%, and 45% at baseline, 1 day and 3 days post‐AMI in db/db mice, respectively. CXCR4 levels are increased 233% at baseline and 54% 5 days post‐AMI in db/db mice. Administration of control MSC led to a significant improvement in ejection fraction (EF) in control mice but not in db/db mice 21 days after AMI. In contrast, administration of SDF‐1:MSC produced a significant improvement in EF in both control mice and db/db mice 21 days after AMI. The SDF‐1:CXCR4 axis is compromised in diabetes, which appears to augment the deleterious consequences of AMI. Over‐express of SDF‐1 expression in diabetes rescues cardiac function post AMI. Our results suggest that modulation of SDF‐1 may improve post‐AMI cardiac repair in diabetes.Stem Cells Translational Medicine 2018;7:115–124 Abstract : The SDF‐1:CXCR4 axis is compromised in diabetes, which appears to augment the deleterious consequences of acute myocardial infarction (AMI). Over‐express of stromal cell‐derived factor‐1 (SDF‐1) expression in diabetes rescues cardiac function post AMI. Results suggest that modulation of SDF‐1 may improve post‐AMI cardiac repair in diabetes.